2020
DOI: 10.1007/s00213-020-05483-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic harmine treatment has a delayed effect on mobility in control and socially defeated rats

Abstract: Introduction Depression is characterized by behavioral, cognitive and physiological changes, imposing a major burden on the overall wellbeing of the patient. Some evidence indicates that social stress, changes in growth factors (e.g., brain-derived neurotrophic factor (BDNF)), and neuroinflammation are involved in the development and progression of the disease. The monoamine oxidase A inhibitor drug harmine was suggested to have both antidepressant and anti-inflammatory properties and may, therefore, be a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…The elevation of ICSS latencies by harmane and harmine is consistent with previous findings that these β-carbolines can suppress motor function in rats as measured using openfield locomotor activity or inactive lever pressing in an operant procedure (Giacobbo et al, 2020;Goodwin et al, 2015;Qiu et al, 2015). The lower potency of harmane and harmine to elevate ICSS latencies compared to ICSS thresholds indicates that motoric effects of these compounds did not confound their effects on thresholds, at least at lower doses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The elevation of ICSS latencies by harmane and harmine is consistent with previous findings that these β-carbolines can suppress motor function in rats as measured using openfield locomotor activity or inactive lever pressing in an operant procedure (Giacobbo et al, 2020;Goodwin et al, 2015;Qiu et al, 2015). The lower potency of harmane and harmine to elevate ICSS latencies compared to ICSS thresholds indicates that motoric effects of these compounds did not confound their effects on thresholds, at least at lower doses.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, another study found that neither harmane nor norharmane pretreatment affected ongoing nicotine self-administration (Hall et al, 2014), and a cocktail of behaviorally active constituents including norharmane, harmane, acetaldehyde, and minor alkaloids (e.g., nornicotine, anabasine) did not alter nicotine's reinforcing effects (Smith et al, 2015). Although harmine produced anhedonic effects in a sucrose preference test (Giacobbo et al, 2020), it has not been evaluated in a model of abuse liability per se.…”
Section: Introductionmentioning
confidence: 97%
“…Depression refers to a severe disabling psychosis that causes severe economic burdens and social consequences globally [1]. Depression is characterized by physiological, cognitive and behavioral changes that threatens patients' overall health [2]. The treatments accessible to depression have developed with the application of ketamine as a fast-acting antidepressant and the refinement of equipment capable of selectively catering to the activity of populations of neuronal subtypes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, various social defeat stress rat models have been developed in recent years, including the CSDS and psychosocial witness stress rat model (Patki, Solanki, & Salim, 2014). Existing studies have shown that behavioral and physiologic characteristics of these rat models are similar to those in mouse models (Arora et al, 2018;Finnell et al, 2018;Giacobbo et al, 2020;Kochi et al, 2017;Morais-Silva et al, 2019;Zaidi et al, 2020), which further confirms the feasibility of CSDS-induced behavioral deficits among different strains.…”
Section: Perspectivementioning
confidence: 77%